PROMOTION GUIDELINE INFLUENCES THE RICE SEED OF RICE SHOP IN DON CHEDI DISTRICT SUPHAN BURI PROVINCE - Mamesuk, Jirapong; Chantanee, Metharat (Journal of Educational Review Faculty of Education in MCU, 2020)
The purposes of this research were 1) to study rice seed buying behavior 2) to study the promotion of the distribution of rice seeds of rice varieties shops. In the district 3) to compare the promotion of rice seed distribution of rice breeders in Don Chedi District. Suphanburi Classified by personal factors 4) to compare the promotion of rice seed distribution of rice breeders in Don Chedi district. Suphanburi Classified by buying behavior of rice seeds The sample used was Customers who buy rice seeds in Don Chedi District 335 people in Suphanburi Province. The tools used in the study were questionnaires with a confidence value of 0.91, the statistics used were percentage, mean, standard deviation, and t-test and F-test. The results showed that 1) The buying behavior of rice seeds was found that the persons who chose to buy were farmers. Choosing to buy the type of rice is RD41 The reason for choosing rice is the quality of the rice seed. The individuals involved in the selection of rice seeds are family members. Time to buy rice seeds 09.01 - 12.00 Channel for buying rice seeds to buy at the store by yourself. And how to buy rice varieties to buy at Malee Rice Varieties 2) Promotion of distribution of rice varieties stores Overall is at a high level. When considering each aspect, it was found that there were 4 areas at a high level: public relations Sales by using salespeople in direct marketing Promotion Advertising aspect was at a moderate level. 3) Comparison of rice seed distribution promotion of rice breeders in Don Chedi District Suphanburi Classified by personal factors found that different sexes. There is a promotion to distribute the seeds of rice varieties stores that differ in advertising. Promotion And sales by using sales staff, age, education level, monthly income status and the number of family members There is a promotion to distribute the seeds of rice varieties stores. Not different in every way 4) Comparison of rice seed distribution promotion of rice breeders in Don Chedi District Suphanburi Classified by rice seed buying behavior, it was found that the persons who bought rice Type of rice varieties selected to buy Reasons for buying rice seeds People who influence rice seed purchase decisions When to buy rice seeds Channel for buying rice seeds And stores that choose to buy different varieties of rice There is a promotion to distribute seeds from rice varieties shops that do not different in all aspects.